Regression of left ventricular hypertrophy in patients with resistant hypertension after renal denervation: the role of hemodynamic and antifibrotic effects - E. I. Solonskaya; O. V. Mochula; V. F. Mordovin; I. V. Zyubanova; M. A. Manukyan; V. A. Lichikaki; A. A. Vtorushina; S. A. Khunkhinova; I. A. Skomkina; A. М. Gusakova; S. Kh. Arsanova; K. V. Zavadovsky; et al. (Российский кардиологический журнал)
Aim. To study the features of regression of left ventricular hypertrophy and magnetic resonance changes of cardiac fibrosis in patients with resistant hypertension (RH) 1 year after renal denervation (RDN) in relation to changes in blood pressure (BP), the level of high-sensitivity C-reactive protein (hsCRP), matrix metalloproteinases 2, 9 (MMP-2, MMP-9), tissue inhibitor of metalloproteinase type 1 (TIMP-1).Material and methods. The study included 42 patients with true RH. The mean age of the patients was 59 (51; 62) years, while half were men. All patients took 3 or more antihypertensive drugs. At baseline and after 12 months, creatinine, hsCRP, MMP-2, MMP-9, TIMP-1 were determined, as well as 24-hour blood pressure monitoring, assessment of left ventricular mass (LVM) and contrast agent accumulation according to cardiac MRI. RDN was performed using Symplicity Fleх (n=18) and Symplicity Spyral (n=24) catheters in accordance with the manufacturer's instructions.Results. A year after RDN, a significant antihypertensive effect and a decrease in heart rate were noted. Sixteen patients (38,1%) reached the target office BP level. After 1 year, a significant decrease in the levels of hsCRP from 2,05 (1,04; 3,28) to 1,64 (0,96; 2,25) mg/l (p=0,045) and MMP-2 from 278,2 (240,9; 353,4) to 265,2 (221,2; 293,2) ng/ml (p=0,018) was detected. There was a trend towards an increase in TIMP-1 and a decrease in MMP-9. According to MRI 1 year after RDN, there was a tendency to increase the contrast agent volume, and there was a pronounced LVM decrease from 228 (180; 295,2) to 204 (169,8; 277) g (p=0,029). Correlation analysis revealed a direct connection between a decrease in LVM and a decrease in SBP and DBP levels, MMP-2 and MMP-9 levels. There was a relationship between a decrease in the contrast agent volume and an increase in TIMP-1 level (r=-0,64; p=0,04).Conclusion. A year after RDN, patients with RH show regression of left ventricular hypertrophy with a pronounced antihypertensive effect and a decrease in collagen production, which could also be significant for suppressing the myocardial fibrosis.